Pengukuran Kualitas Website E-Procurement Menggunakan Standart ISO/IEC 25010 - Faris Hudaifi, Afif; Retnoningsih, Dwi; Charolina, Astri (Jurnal Algoritma, 2025)
The development of technology and the growing needs of users make website quality evaluation crucial to ensure optimal performance and adequate security. The E-Procurement system of PT ASDP Indonesia Ferry (Persero) is an online procurement platform for goods and services designed to enhance efficiency, transparency, and accountability in the procurement process. This study aims to assess the quality of the E-Procurement website of PT ASDP Indonesia Ferry using the international ISO/IEC 25010 standard, focusing on four key aspects: functional suitability, performance efficiency, compatibility, and security. The research method combines quantitative and qualitative approaches through testing with GTMetrix, Google PageSpeed Insights, Pingdom, ImmuniWeb, as well as a Mean Opinion Score (MOS) survey of internal users. The findings indicate that functional suitability and compatibility fall into the “very good” category. Performance efficiency varies: low scores on GTMetrix (9%), but high scores on Google PageSpeed Insights (94) and Pingdom (95). Security was rated “C” due to the use of outdated libraries and suboptimal cookie configurations. Recommendations include optimizing loading speed, updating security components, and improving accessibility and SEO. From an academic perspective, this study reinforces the application of the ISO/IEC 25010 standard as a framework for evaluating the quality of web-based software and demonstrates the integration of automated testing methods and user perceptions as a comprehensive approach in software engineering. This research is expected to serve as a reference for developing E-Procurement websites that are more efficient, secure, and compliant with software quality standards.